2022
DOI: 10.1186/s13256-022-03333-7
|View full text |Cite
|
Sign up to set email alerts
|

Progressive multifocal leukoencephalopathy in a patient with novel mutation in the RAC2 gene: a case report

Abstract: Background Progressive multifocal leukoencephalopathy is a rare demyelinating disease that is often secondary to lytic destruction of oligodendrocytes and, to a lesser extent, to astrocytes’ response to human neurotrophic John Cunningham polyomavirus. Any underlying congenital disorder of primary or secondary immunodeficiency may predispose to virus infection and possible invasion of the brain. We present the first reported case of progressive multifocal leukoencephalopathy due to a mutation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Alkhairyet et al reported in 2014 the homozygous loss-of-function mutation in the RAC2 gene, (W56X) causes: CVID, glomerulonephritis, coagulopathy, multiple hormone deficiencies potentially on the autoimmune basis and abnormalities of neutrophil granules [ 32 ]. Among patients reported to date due to RAC2 mutations [ 5 , 33 ], recurrent sinopulmonary infections was the major clinical manifestation during their first admission. Despite the presence of various types in these patients, only 2 family cases (sister/brother) with W56X diagnosed with post streptococcal glomerulonephritis (PSGN) [ 34 ].…”
Section: Ieis With Renal Manifestationsmentioning
confidence: 99%
“…Alkhairyet et al reported in 2014 the homozygous loss-of-function mutation in the RAC2 gene, (W56X) causes: CVID, glomerulonephritis, coagulopathy, multiple hormone deficiencies potentially on the autoimmune basis and abnormalities of neutrophil granules [ 32 ]. Among patients reported to date due to RAC2 mutations [ 5 , 33 ], recurrent sinopulmonary infections was the major clinical manifestation during their first admission. Despite the presence of various types in these patients, only 2 family cases (sister/brother) with W56X diagnosed with post streptococcal glomerulonephritis (PSGN) [ 34 ].…”
Section: Ieis With Renal Manifestationsmentioning
confidence: 99%